The future of domestic capital markets in developing countries - Litan, Robert E., 1950-; Pomerleano, Michael; Sundararajan, Vasudevan (Brookings Institution Press, 2003)
This volume brings together financial sector experts and leaders from around the world to provide practical guidance on strategies such as nuturing issuers, improving rules and institutions, addressing regulatory challenges and sequencing reforms.